2019
DOI: 10.25095/mufad.536072
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’deki Yabancı Sermayeli Bankaların CAMELS Analizi ile Performanslarının Ölçümü

Abstract: In this study, aimed that compare of the performance of foreign capital banks in Turkey. 12 foreign capital banks in Turkey were analysis by CAMELS rating system. The performance of banks from 2010 to 2016 years were measured at 23 financial ratios. The analysis results show that performance decreased in % 50 of foreign capital banks in 2016 basis 2010. Generally, after 2014; profitability, quality of management and capital qualifications have decreased. It has been revealed that the liquidity adequacy and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…To compare the performances of foreign banks, Uslu [12] analyzed the data of 12 foreign banks between the years 2010-2016 with the CAMELS rating system. The data obtained from the research revealed that, taking 2010 as the basis, half of the foreign banks' performance declined in 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To compare the performances of foreign banks, Uslu [12] analyzed the data of 12 foreign banks between the years 2010-2016 with the CAMELS rating system. The data obtained from the research revealed that, taking 2010 as the basis, half of the foreign banks' performance declined in 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Karaca (2018) veUslu (2019) tarafından yapılan çalışmalarda CAMELS kapsamında belirlenmiş finansal rasyolar hesaplanmış ve bu rasyolar ağırlıklandırılarak her banka için bir derecelendirme notu belirlenmiştir. Yine bankalar üzerinde yoğunlaşanTosuner, vd.…”
unclassified